2018
DOI: 10.4103/jovr.jovr_213_16
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing graft endothelial cell density after descemet stripping automated endothelial keratoplasty

Abstract: Purpose:To determine the factors that influence the endothelial cell density (ECD) of donor grafts after Descemet stripping automated endothelial keratoplasty (DSAEK).Methods:This retrospective, interventional case series comprised 77 eyes of 64 patients who underwent DSAEK. Confocal microscopy was performed at the final follow-up examination to evaluate the endothelial cell count, cell morphology, and graft thickness. Univariate and multiple linear regression analyses were used to investigate recipient-, dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Other studies have observed that the gender of the donor and the recipient did not influence the risk of graft failure or ECD reduction in DSAEK patients which supports our findings (Javadi et al. 2018; Madzak & Hjortdal 2018). Still, the influence of sex match/mismatch between donor and recipient needs to be further studied.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other studies have observed that the gender of the donor and the recipient did not influence the risk of graft failure or ECD reduction in DSAEK patients which supports our findings (Javadi et al. 2018; Madzak & Hjortdal 2018). Still, the influence of sex match/mismatch between donor and recipient needs to be further studied.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Potapenko et al found no difference in graft survival for matching of genders between the donor and recipient with a 2-year survival analysis of 1789 DSAEK patients, but they did observe corneas from male donors to have a worse survival rate independent of recipient gender (Potapenko et al 2017). Other studies have observed that the gender of the donor and the recipient did not influence the risk of graft failure or ECD reduction in DSAEK patients which supports our findings (Javadi et al 2018;Madzak & Hjortdal 2018). Still, the influence of sex match/ mismatch between donor and recipient needs to be further studied.…”
Section: Discussionsupporting
confidence: 89%
“…Clinically, we obtained an average ECD loss of 46.3% at month 6 and 49.1% at month 12, which was similar (or slightly higher) than other cases found in the literature. For instance, the ECD loss reported after 12 months from UT-DSAEK surgery was 49% by Feng et al, 43 38.9% by Graffi et al, 44 and 35.6% by Busin et al 8 For DSAEK, van Cleynenbreugel et al 45 reported a 40.2% loss after 6 months, Guerra et al 46 a 34.9% loss after 12 months, and Javadi et al 47 a 42.8% at 2 years of follow-up. We observed that our cohort showed a large variability on ECD loss at the different time intervals, without a clear pattern ( Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Sketching the limits of cultured CECs expansion is an unavoidable safety issue to be addressed in order to advance onto an in-vivo model. Our study allows guaranteeing cellular and tissular quality, as well as functionality for transplantation so further efforts might focus on improving surgery practices [33] and suggesting further monitoring techniques.…”
Section: Discussionmentioning
confidence: 99%